Perilaku Produksi Industri Batik Kota Pekalongan Menurut Etika Produksi Islam - Tamamudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Pekalongan known as a city whose economies are based on the batik industri, for the quality of the city of Pekalongan batik is in excellent condition, is evidenced by the absence of some in Pekalongan batik industri that already exports its products to various countries. Ethics is very important to be applied in the production process to minimize any production activities that cause harm. Greed of man and the love of the world is one thing that makes people act not in accordance with the rules or ethics, so that the rules of values and norms have a very important position in the control action in order not to cause dangerous to other human beings, in running the batik industri, the company always trying to follow the principle of balance in all aspects. Balance is the key to the survival of the company.